Functional and smart materials - Davim, J. Paulo; Prakash, Chander; Singh, Sunpreet , 1989- (Boca Raton, FL : CRC Press, 2021)
"This book presents a comprehensive and broad-spectrum picture of the state-of-the-art research, development, and commercial prospective of various discoveries conducted in the real-world of functional and smart materials. The book presents the various synthesis and fabrication route of functional and smart materials for universal applications such as material science, mechanical engineering, manufacturing, metrology, nanotechnology, physics, chemical, biology, chemistry, civil engineering, and food science. The content of this book opens the various scientific horizons which are proved to be of utmost beneficial for uplifting the standards of the day-to-day practices in the biomedical domain. Noticeably, myriads of innovations in the materials science and engineering are transforming our day-to-day life in an extraordinary manner. The book has captured emerging areas of materials science and advanced manufacturing engineering and presents the recent trends in research for young researchers, field engineers, and academic professionals"-- Provided by publisher
1. Electrochromics for smart windows: oxide-based thin films -- 2. Polymeric biomaterials in tissue engineering -- 3. Amorphous semiconductors: past, present, and future -- 4. Promise of self-lubricating aluminium-based composite material -- 5. Energy materials and energy harvesting -- 6. Advanced processing of superalloy for aerospace industries -- 7. Review on rheological behavior of aluminum alloys in semi-solid state -- 8. Bio-nanomaterials: an inevitable contender in tissue engineering -- 9. Biomaterials -- 10. Characterisation and optimisation of TiO2/CuO nanocomposite for effective dye degradation from water under simulated solar irradiation -- 11. Dual applicability of hexagonal pyramid-shaped nitrogen-doped ZnO composites as an efficient photocatalyst
Includes bibliographical references (216-217 pages) and index
Keywords: Smart materials